Plasma methods for efficiency of solid fuel utilization improvement - Karpenko, E.I.; Ustimenko, A.B. (Recent Contributions to Physics, 2020)
After oil, coal makes the largest contribution to the global balance of primary energy production. Thus, since the first oil crisis, global coal consumption has increased by 45%, and reached a share of 22% in the total production of primary energy resources (PPER). Coal is most used in power generation: about 40% of the world's electricity is generated by burning coal. Necessity of fuel utilization new technologies development is justified. One of the promising technologies is plasma ignition and incineration of power coals, application of which allows substitution of expensive oil by cheap coal in thermal power plants. Plasma technology of oil-free boilers start up and pulverized coal flame stabilization has been tested in thermal power plant of Russia, Republic of Kazakhstan, Ukraine, China, Mongolia, Korea, Slovakia and Serbia. Theoretical and experimental methods of investigation of coal plasma ignition, thermochemical preparation, incineration and gasification are described. Methods of plasma-fuel systems computation are discussed. Ensuring eco-economical advantages in compare with conventional technologies of fuel utilization basic principles of plasma-fuel systems functioning are presented.